Development of urban agglomerations as one of the directions of the strategy of spatial development of Russia - N. N. Musinova (Вестник университета, 2019)
In the last four years in the Russian Federation steps to spatial arrangement of the country are taken. One of the project directions of strategy of spatial development of the Russian Federation until 2025, namely – formation and management of development of city agglomerations has been examined in the article. The problems have been highlighted, the purposes and the mechanism of management have established, the changes made to Federal law dated October 6, 2003 No. 131-FZ «On the General Principles of the Organization of Local Self-Government in the Russian Federation» at a development stage of the studied direction of strategy have been considered and an assessment has been given them.